FORMULATION AND QUALITY EVALUATION OF CHOCOLATE FLAVOURED RICE BASED MEAL REPLACER FOR ADULTS - ATHIRA RAJ,; SUMAN K.T., (The Journal of Research ANGRAU, 2025)
This research (2021-2024) aimed to create nutritious meal replacers for adults that offer balanced nutrients. The meal replacer powder was developed using rice, ragi, and other functional ingredients at different levels (MR-T1 to MR-T10). Meal replacer powder was prepared using these treatments and subjected to organoleptic evaluation. The best treatment was selected through sensory evaluation using a scorecard with a nine-point hedonic scale. The maximum score for all the organoleptic attributes was obtained for meal replacement powder (MR-T5), which were prepared by blending rice (50%), ragi (10%), jackfruit flour (15%), skimmed milk powder (15%), soy protein isolate (5%) and other ingredients like peanut and rice bran flour (5%). The nutritional composition of the selected meal replacement powder included  65.173g of carbohydrates, 22.88g of protein, 2.323g of fat, 4.137g of fibre, and 2.39g of total ash per 100g, offering 371.92 kcal of energy. Nutritious meal replacers made from locally sourced ingredients can be promoted as a healthy and convenient option for maintaining a balanced diet in busy lifestyles.